Cross Sectional Study on Estimation of Stature from Index, Middle and Ring Finger in Adult Population of Hyderabad Telangana. (Medico Legal Update, 2022)
Cross sectional study on estimation of stature from length of fingers (Index, Middle and Ring finger of both the hands) was conducted on 150 individuals in the region of Hyderabad, Telangana. Study results showed that there is a significant correlation between length of fingers and stature, Index and middle finger lengths are more reliable than a ring finger length was observed in our study. The height of the individual is approximately 23 times the length of the ring finger, 21 times the length of the middle finger and 22 times the length of the index finger. Standard error of 1.34 to 1.60, R square less than 0.5 and P value less than 0.001 shows statistical significance of our study. The data was statistically analyzed by using SPSS (version-25) software. The formula for linear regression for estimating the height is y = a + (b x).Regression formulae for total population for right index finger is y = 69.75 + (13.75 x), left index finger is y = 66.05 + (14.15 x), right middle finger is y = 63.75 + (13.21 x), left middle finger is y = 62.79 + (13.25 x), right ring finger is y = 71.88 + (13.24 x) and left ring finger is y = 71.84 + (13.22 x). A separate linear regression equation for male and female found more accuracy than equation for total population was observed in our study. Calculated statures from these equations are close to the actual height, only ±5cm difference was observed in most of the individuals.